Study on insect pest on paddy field:stem borer - Nuraini Nordin (2014)
Stem borer is one of the serious rice pest attacking paddies in Asia especially in East Asia. A research was conducted in Rantau Panjang, Kelantan along the time interval from September 2013 until December 2013 to study the serious infestations of stem borers and to identify the species varieties of stem borers present. The research was done to determine the growth stage of paddy heavily infested by stem borers. There were three growth stage of the paddy which the research had been carried out which were the vegetative stage, the reproductive stage and the ripening stage. The trial was arranged in a 3 split plot design with 6 replications. The population of the paddy and the damage was recorded. Damage paddies were then collected from each plot and then the infestation was determined. The most heavily infested stage was recorded. Results showed that the dominant species of stem borer was yellow stem borer (Scirpophaga incertulas). Stem borer infestation at the second growth stage, the reproductive stage was higher compared to those found at the first and third growth stage. Climatic factors such as temperature, relative humidity, rainfall may affect the distribution, development, reproduction, population dynamics, and outbreaks of stem borers. Results showed that the major stem borers' infestation was during dry season, dry weather, high temperature and low humidity. The present study implies that adjustment of planting time is the most feasible effort to reduce stem borer infestation. Besides that, the study state high temperature and to rainfall can cause a severe stem borer infestation.